New species of the genus Hyleoglomeris from Korea (Diplopoda: Glomerida: Glomeridae) - Mikhaljova, Elena V.; Lim, Kil-Young (Zootaxa, 2006)
Five new species of the millipede genus Hyleoglomeris Verhoeff, 1910 (Glomeridae) are described from South Korea: Hyleoglomeris unicolorata sp. n., H. buana sp. n., H. obscura sp. n., H. confragosa sp. n. and H. alutacea sp. n. Several earlier misidentifications are corrected. All currently known Hyleoglomeris species from Korea are keyed, including new species.